Effect of Calf Stretching Versus Heel Walking in Nocturnal Leg Cramps in Older Individuals: Life Sciences-Physiotheraphy - Vijay Pawar, Ashwini; Bathia, Dr. Khushboo; Rayjade, Dr. Amrutkuvar; Patil, Dr. Smita (International Journal of Life Science and Pharma Research, 2021)
Nocturnal leg cramps are sudden, episodic, painful, sustained and involuntary muscle contractions of the calf muscles, hamstrings, or foot muscles. The objective of this study was to find out the effect of calf stretching versus heel walking in nocturnal leg cramps in older individuals and aware them about this condition to avoid further complications. To find the effect of calf stretching versus heel walking in nocturnal leg cramps in older individuals. Study was conducted with 50 subjects in and around Karad. Subjects were selected as per inclusion and exclusion criteria and consent was taken. Included participants will be divided in 2 groups by simple random sampling method. Pre, and post assessment will be taken before treatment and after 6 weeks of the treatment respectively with the help of outcome measures. Group A was instructed to perform calf stretching and group B was instructed to perform heel walking. After pre-post assessment data was analysed with help of appropriate statistical methods. Statistical analysis of the recorded data was done by using the software SPSS version20. Arithmetic mean and standard deviation was calculated for each outcome measure. Arithmetic mean was derived from adding all the values together and dividing the total number of values. MS Excel was used for drawing various graphs with given frequencies and the various percentages that were calculated with the software. According to pre-test and posttest analysis the result showed that calf stretching is statistically significant in reducing nocturnal leg cramps than heel walking in older individuals. Calf stretching is more effective than heel walking in older individuals having nocturnal leg cramps. The impact of calf stretching on nocturnal leg cramps needs to be taken into consideration